Investigating an Enhanced Contour Blasting Technique Considering Rock Mass Structural Properties - Askar Imashev; Aibek Mussin; Amoussou Coffi Adoko (Applied Sciences)
When excavating tunnels and underground openings with the drill-and-blast method, minimizing excavation overbreak is vital, as it reduces the costs associated with excavation stability, mucking, and rock support. Overbreak in excavations not only causes safety concerns but also increases the cost of construction and completion time. This paper proposes a contour blasting design in which the parameters are optimized based on the rock’s structural properties. Numerical modeling was used to identify the possible damage zones of rock with a change of the seismic load due to blasting. The results were used as input for the design of the proposed contour blasting with a low-brisance explosive. Experimental blasting tests were conducted at the Akbakai mine, located in Kazakhstan, and the performance of the design was examined. The proposed contour blasting was compared with the standard blasting method. The results indicated that the cross-section of excavation with the conventional blasting method varied between 10.5 and 12.1 m2, indicating an overbreak between 17 and 34%. However, with the suggested contour blasting, the overbreak was less than 13%. It was concluded that charging contour boreholes with low-brisance explosives is an effective method of reducing overbreak due to excessive explosive loads on the contour massif, which can improve the safety and profitability of mining operations.